G512(P) #Choosepaediatrics- career's fair!. (25th October 2020) - Molloy, S; Skehin, K; Lewis, J; Christie, S; Thompson, A; Bourke, T; Richardson, J
Abstract : Background: With the launch of the #ChoosePaediatrics Campaign, there is national recognition that recruitment and retention are the biggest issues facing the future of the Royal College of Paediatrics. There has been a 30% decline in applications and the drop-out rate is rapidly rising. Resultant rota gaps, poor work/life balance and burnout in a climate of political uncertainty and under-resourced workforce mean trainees feel underappreciated. Career opportunities are being forfeited to provide the high-quality service expected by the public. However, we too deserve the best! Life passes at such a pace, we find ourselves thinking....what if. As a pivotal part of RCPCH, trainees in Northern Ireland decided to host a careers fair. A fun day showcasing the resources and opportunities available, to prepare and improve our futures academically, physically and mentally. Aims: To provide support for all trainees to facilitate a smoother transition through training. To showcase the available opportunities within paediatric training. To provide an enjoyable, networking opportunity for all paediatric affiliations within NI. Methods: Designed as a ST1–8 regional teaching day. Recruitment of medical director, school tutors and senior trainees collaborating inspirational and informative discussions on leadership, curriculum, governance, careers and wellbeing. An afternoon funfair theme emulated via career's stalls featuring paediatric subspecialties, district general hospitals, academia, NI library, BMA and RCPCH, principally creating an opportunity to network. Responses evaluated via online feedback Results: NI's inaugural career's fair was a huge success. 70% of trainees attended, all rating it as excellent/very good. Highlights included; 'better understanding of future opportunities', 'great networking environment' and 'the ice-cream'. Further feedback included; 'inspired to be proactive about my goals' and a senior-trainee shared 'I wish I'd attended this earlier'. Participation by trainers was almost 100%, viewed as 'best thing we have done in years'. Suggested improvements were a larger venue and a two-day event. Conclusions: A regional career's day is an excellent opportunity to boost morale, tailor careers advice and network. It was an uplifting day, taking a step back from workload to promote paediatrics and all it has to offer. We are the future of the RCPCH.... #ChoosePaediatrics!!